Effect of Long-Term Supplementation of AZOMITE (Hydrated Sodium Calcium Aluminosilicate) in Finishing Diets on Growth Performance, Dietary Energy, and Carcass Yield of Hairy Lambs - Claudia A. Vizcarra-Chávez; Jesús D. Urías-Estrada; Elizama Ponce-Barraza; Alfredo Estrada-Angulo; Yesica J. Arteaga-Wences; Beatriz I. Castro-Pérez; Jorge L. Ramos-Méndez; Luis Corona; Armando Gomez-Vázquez; Alejandro Plascencia (Animals)
The aim of this study was to evaluate growth performance, dietary energy utilization, and carcass characteristics (carcass weight, dressing percentage, and visceral organ mass) of feedlot lambs fed different levels of AZOMITE (AZO), a source of volcanic clay composed of hydrated sodium calcium aluminosilicate, the same as that included in a finishing diet. For this reason, 36 Pelibuey × Katahdin crossbred intact male lambs (18.81 ± 3.04 kg initial weight) were used in a feeding trial lasting 81 d. Lambs were grouped by initial weight and assigned within six weight groupings to 18 pens in a randomized complete block design. Diets, offered ad libitum, were corn-based finishing diets with an 88:12 concentrate-to-forage ratio supplemented as follows: 1) no AZO inclusion (CTRL), 2) AZO inclusion at a 0.75% level (0.75AZO) in diet dry matter, 3) AZO inclusion at a 1.50% level (1.5AZO) in diet dry matter. Cracked corn was replaced by AZO. After the feeding trial was finished, lambs were slaughtered and carcass weight was registered and dressing percentage was calculated. The data were analyzed as a randomized complete block design, with the pen as the experimental unit. Water consumption and dry matter intake were not affected (p ≥ 0.11) by supplemental AZO. The incorporation of AZO into the diet increased gain efficiency and observed dietary net energy (NE), being maximal with 0.75% AZO inclusion (quadratic effect, p = 0.02). The observed-to-expected dietary NE in the control group was as anticipated (1.00) according to the estimated energy based on the ingredient composition in diet, while in the 0.75AZO group, the observed dietary energy was 6% above expected, indicating a greater efficiency in energy utilization destined to growth (quadratic effect, p = 0.006). Lambs that were fed the AZO treatment showed an improvement (linear effect, p = 0.04) in hot carcass weight (HCW), and tended (linear effect, p = 0.06) to improve dressing percentage (DP) as AZO was increased in the diet. Visceral organ mass was not affected by the treatments. It is concluded that AZOMITE clay can be included up to 1.5% in finishing diets for lambs without negative effects on the intake of water and feed. Lambs that received diets supplemented with 0.75% AZO showed greater improvements in feed efficiency and dietary energy utilization, but an inclusion of 1.50% resulted in greater improvements to HCW and DP. This is the first report regarding the effects of AZO supplementation in the dietary energy utilization of fattening hairy lambs. Further research about the effects of AZO supplementation on ruminal and total tract digestion, carcass and meat quality, and the health of lambs is needed in order to more deeply understand the effects of AZO on its productivity performance.